2021
DOI: 10.1038/s41598-021-88042-9
|View full text |Cite
|
Sign up to set email alerts
|

The effect of marital status on stage at diagnosis and survival in Saudis diagnosed with colorectal cancer: cancer registry analysis

Abstract: Colorectal cancer (CRC) is the most common cancer in males and third in females in Saudi Arabia, with the majority (66%) diagnosed at a late stage. We evaluated the effect of marital status on stage at diagnosis and CRC survival. We hypothesized that married patients would be more likely to present at an early stage and have higher survival than unmarried patients. The Ministry of National Guard-Health Affairs (MNG-HA) cancer registry was used to identify patients diagnosed with CRC from 2009 to 2017. A compet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 44 publications
2
13
0
Order By: Relevance
“…Several clinical studies have shown that socio‐psychosocial factors are important prognostic factors in a variety of tumor types in both adults and adolescents, 21–24 and marital status is one of the most important socio‐psychosocial factors 25–27 . Recent studies have focused on marital status and cancer, and the results suggest that married patients have significantly better survival than unmarried patients 27–29 . However, to date, there have been few studies on the effect of marital status among patients with RPLs.…”
Section: Introductionmentioning
confidence: 99%
“…Several clinical studies have shown that socio‐psychosocial factors are important prognostic factors in a variety of tumor types in both adults and adolescents, 21–24 and marital status is one of the most important socio‐psychosocial factors 25–27 . Recent studies have focused on marital status and cancer, and the results suggest that married patients have significantly better survival than unmarried patients 27–29 . However, to date, there have been few studies on the effect of marital status among patients with RPLs.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, women with BMI ≥ 23 at age 18 had a 63% higher risk of early-onset CRC compared to women with a BMI of 18.5-20.9 (10). Third, there is currently no population-based screening for CRC in Saudi Arabia, leading to delayed CRC detection, increased late-stage diagnosis, and poor survival across all age groups (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…Several epidemiologic cancer studies have found marital status to be an independent prognostic factor. Married patients were found to have a lower overall and cancer speci c mortality, compared to their non married counterparts [18][19][20][21][22][23][24][25][26][27]. This was mainly thought to be due to better social support among married patients.…”
Section: Discussionmentioning
confidence: 99%